Media markets, special interests, and voters (2012)
This paper examines the role of mass media in countering special interest group influence. I use the concentration of campaign contributions from Political Action Committees to proxy special interests' capture US Senate candidates from 1980 to 2002, and compare the reaction of voters to increases in concentration in two different types of media markets - in-state media markets and out-of-state media markets. Unlike in-state media markets, out-of-state markets focus on neighboring states' politics and elections. Thus, if citizens punish political capture, increases in concentration of special interest contributions to a particular candidate should reduce his vote share in in-state counties relative to the out-of-state counties, where the candidate receives less coverage. I find that a one standard deviation increase in concentration of special interest contributions to incumbents reduces their vote share by about 0.5 to 1.5 percentage points in in-state counties relative to the out-of-state counties. Results are similar in specifications that rely solely on variation in concentration across time within the same county, and when the sample is limited to in-state counties that are contiguous to out-of-state counties and have similar demographic structures. A placebo test where in-state counties bordering out-of-state ones are compared to other in-state counties shows no effect, confirming the identification hypothesis that the results are not driven by geographic characteristics or distance from the media center of the state.